2007
DOI: 10.1007/bf02877703
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bone mineral density and biochemical markers of bone turnover in hemodialysis patients

Abstract: End-stage renal disease is closely associated with changes in bone and mineral metabolism. In recent times, osteoporosis has become important among hemodialysis (HD) patients. In this study, the investigators sought to evaluate the relationship between bone mineral density (BMD) and biochemical markers of bone turnover among HD patients. A total of 70 uremic patients on a maintenance HD program for at least 1 y were enrolled in the study. All patients were treated with conventional bicarbonated HD for 5 h thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
14
1
1
Order By: Relevance
“…Although the distorted bone and mineral metabolism in MHD patient has been widely studied, the risk factors and predictors of decreased BMD in MHD patients are not well understood 13,14 . Given the observed association between serum AlkPhos and fracture in recent studies, 5,13 we hypothesized that the increased serum AlkPhos may be a marker of decreased BMD in MHD patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the distorted bone and mineral metabolism in MHD patient has been widely studied, the risk factors and predictors of decreased BMD in MHD patients are not well understood 13,14 . Given the observed association between serum AlkPhos and fracture in recent studies, 5,13 we hypothesized that the increased serum AlkPhos may be a marker of decreased BMD in MHD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the distorted bone and mineral metabolism in MHD patient has been widely studied, the risk factors and predictors of decreased BMD in MHD patients are not well understood 13,14 . Given the observed association between serum AlkPhos and fracture in recent studies, 5,13 we hypothesized that the increased serum AlkPhos may be a marker of decreased BMD in MHD patients. To test this hypothesis, we examined the association of serum AlkPhos and BMD in a cohort of MHD patients in whom other potential correlates of renal osteodystrophy and metabolic disorders including serum parathyroid hormone (PTH) and nutritional and inflammatory markers were also examined.…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, no significant relationship was found between iPTH and BMD (31,34). As did Sit et al (35) in their study of 70 hemodialysis patients, and Huang GS al. (1) in their study of 63 patients who had been on hemodialysis for at least 6 months (1), we also found no relationship of BMD with calcium and phosphorous.…”
Section: Discussionmentioning
confidence: 80%
“…Grzegorzewska et al (14) reported that elevated PTH level is important in prediction of BMD with the lowest values seen in patients with the highest PTH levels. But there are studies showing no relation (9,19,20) or negative correlation also (7,(15)(16)(17)(18). Beyond the speculations related to the geographical or racial differances, these variations may be associated to PTH level.…”
Section: Figure 2 the Femur And Lumbar T Scores According To The Bmdmentioning
confidence: 96%